High-nickel single-crystal positive electrode material as well as preparation method and application thereof
Through the high-active precursor precursor precursor precursor precursor and the two sintering and coating processes, the problems of structural stability and side reactions of ultra-high nickel positive electrode materials during circulation are solved, and the circulation performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202311372375.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
Ultra-high nickel positive electrode materials are prone to cracks, crystal structure phase change and side reactions with electrolyte during the circulation process, resulting in poor circulation performance and the material has strict requirements on the environment, which makes it easy to absorb water and react to lead to increased residual alkali.
The high-active precursor precursor precursor is adopted to react the precursor material with the first metal additive to generate a high-active oxide precursor, which promotes the Li+ deintercalation when the single crystal semi-finished product is sintered with the lithium salt, reduces the mixed discharge of lithium nickel and residual alkali, and performs two sintering and coating processes to reduce the side reaction between the material and the electrolyte.
It effectively reduces the generation of particle cracks, inhibits the phase change of the crystal structure, reduces the side reaction between the material and the electrolyte, improves the conductivity of Li+ and the interface stability of the material, thereby improving the cycling performance of the battery.
Smart Images

Figure CN119890302A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a high-nickel single crystal positive electrode material and a preparation method and application thereof. Background Art
[0002] NCM811 batteries and NCA batteries with a nickel content of 80% have been mass-produced and supplied. In order to further reduce costs and increase energy density, new high-nickel batteries with a nickel content of more than 90% have become the current research and development focus. Ultra-high nickel layered materials have become one of the important sources of positive electrode materials for lithium-ion batteries due to their high energy density and price advantages. With the increase of nickel content in the material, the structural stability of the material phase will also deteriorate during the cycle. For example, more microcracks will appear in the material, which will also aggravate the interface side reaction between the electrode and the electrolyte. The surface of the particles will undergo a phase transition from layered to spinel and rock salt phases. The phase transition is also accompanied by the release of a certain amount of oxygen from the material, resulting in a decrease in the structure and cycle stability of the positive electrode material. At the same time, ultra-high nickel materials have more stringent requirements on the environment, and are extremely easy to absorb water and react with CO2 in the air, resulting in an increase in residual alkali. Therefore, it is particularly important to solve the problems of increased residual alkali and poor cycle performance caused by ultra-high nickel positive electrode materials.
[0003] CN 116497450A discloses a method for preparing a single crystal ternary material, a single crystal ternary material and a lithium ion battery, so as to solve the problems of poor precursor adaptability, difficulty in controlling the sintering temperature and performance of the single crystal ternary material, high residual alkali content and poor rate and low temperature performance in the method for preparing the single crystal ternary material in the prior art. The spherical oxide precursor that meets the particle size requirements of the single crystal ternary material can be obtained by pre-sintering and crushing. The spherical oxide precursor has a morphology similar to that of the single crystal ternary material, has fewer grain boundaries inside the particles, and is conducive to rapid diffusion of lithium ions from lithium oxide to the inside of the oxide precursor to form a ternary material when mixed with lithium oxide for sintering. The spherical particle design is conducive to rapid sliding of the positive electrode material when the material pole piece is rolled, and the particles are in close contact, thereby improving the compaction density and rate performance. However, the oxide precursor is obtained after the pre-treatment and sintering of the ternary precursor, and the oxide precursor has low activity, which is not conducive to the deintercalation of lithium ions when sintering with lithium salt.
[0004] Based on the above research, it is necessary to provide a method for preparing a high-nickel single crystal positive electrode material, which can effectively mitigate the generation of particle cracks, inhibit the phase change of the crystal structure, reduce the side reactions between the material and the electrolyte, and improve the cycle performance of the positive electrode material. Summary of the invention
[0005] The purpose of the present invention is to provide a high-nickel single crystal positive electrode material and a preparation method and application thereof, and in particular to an ultra-high-nickel single crystal positive electrode material and a preparation method and application thereof. The preparation method first prepares a high-activity precursor, which is beneficial to the sintering of the single crystal semi-finished product with the lithium salt. + Deintercalation and subsequent coating can reduce side reactions between the material and the electrolyte, while improving the interface stability of the material, thereby enhancing the cycle performance of the battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a high-nickel single crystal positive electrode material, the preparation method comprising the following steps:
[0008] (1) mixing and pre-calcining a precursor material and a first metal additive to obtain an active oxide precursor;
[0009] (2) mixing the lithium salt and the active oxide precursor of step (1) and sintering once to obtain a semi-finished product;
[0010] (3) The coating agent and the semi-finished product of step (2) are mixed and subjected to secondary sintering to obtain the high-nickel single crystal positive electrode material.
[0011] The present invention adopts a high-activity precursor pretreatment sintering process, firstly through the reaction of the precursor material and the first metal additive, to generate a highly active oxide precursor, which is beneficial to the sintering of the single crystal semi-finished product with the lithium salt. + Deintercalation reduces lithium-nickel mixing, inhibits phase change of crystal structure, reduces residual alkali, and performs two sintering and coating processes to reduce side reactions between materials and electrolytes, thereby increasing Li + The conductivity of the material is improved, while the interface stability of the material is improved, thereby enhancing the cycle performance.
[0012] Preferably, the precursor material in step (1) comprises a high nickel hydroxide precursor.
[0013] Preferably, the general formula of the high nickel hydroxide precursor is Ni x Co y Mn z (OH)2, wherein x+y+z=1, x>0.90, for example, it can be 0.91, 0.92, 0.93, 0.94, 0.95 or 0.96, y<0.09, for example, it can be 0.02, 0.04, 0.06 or 0.08, z<0.09, for example, it can be 0.02, 0.04, 0.06 or 0.08, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0014] The preparation method of the present invention does not involve water washing, and the positive electrode material prepared by the water-free washing process has an ultra-high nickel and low cobalt ratio. Both the low cobalt and water-free washing processes reduce costs, have a short preparation cycle, a simple process, and can be industrialized. Therefore, the preparation method of the present invention can specifically solve the problems existing in ultra-high nickel single crystal positive electrode materials.
[0015] Preferably, the median particle size of the precursor material in step (1) is 2.5-5 μm, for example, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, and the BET is 11-20 μm. 2 / g, for example, it can be 11m 2 / g, 15m 2 / g or 20m 2 / g, bulk density ≥1.1g / cm 3 , for example, it can be 1.1 g / cm 3 , 1.3g / cm 3 , 1.5g / cm 3 or 2.0g / cm 3 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0016] Preferably, the molar ratio of the precursor material to the first metal additive in step (1) is 1:(0.001-0.050), for example, it can be 1:0.001, 1:0.01, 1:0.02, 1:0.03, 1:0.04 or 1:0.05, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] The amount of the first metal additive added in the present invention will affect the activity of the oxide precursor. If the amount of the first metal additive added during pre-firing is too small, the activity of the oxide precursor will be low, the structural stability of the positive electrode material and the electronic conductivity of the material will be low, thereby causing a decrease in the cycle electrical performance; if the amount of the first metal additive added during pre-firing is too much, the electrical performance will be reduced. Due to the formation of impurity phases (LiMO2 and Li5MO4), the residual lithium on the positive electrode surface will be significantly increased, thereby reducing the initial capacity of the material.
[0018] Preferably, the metal element in the first metal additive in step (1) includes any one of Y, Sr, Zr, Ti, W, Al or Mg, or a combination of at least two of them.
[0019] Preferably, the pre-calcination temperature in step (1) is 450-600°C, for example, 450°C, 500°C, 550°C or 600°C, and the pre-calcination time is 4-8h, for example, 4h, 6h or 8h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] The pre-firing temperature of the present invention will also affect the activity of the oxide precursor. If the pre-firing temperature is too low, since the hydroxide precursor is nickel hydroxide with a melting point of 230°C, the hydroxide cannot be better converted into an oxide and an active oxide precursor cannot be formed. At the same time, the lithium hydroxide cannot be completely melted and penetrated into the interior of the particles, and the residual lithium remains on the surface, resulting in excessive residual lithium in the sintered product and reduced cycle electrical performance. If the pre-firing temperature is too high, the precursor is converted from a layered structure to a rock salt phase structure. It is difficult for the lithium salt to react with the rock salt phase structure precursor to generate a positive electrode material with a good layered structure. The generated material has serious Li / Ni mixing, resulting in reduced cycle electrical performance.
[0021] Preferably, the pre-firing atmosphere in step (1) comprises an oxygen-containing atmosphere, and the oxygen concentration of the oxygen-containing atmosphere is ≥ 95%, for example, it can be 95%, 96%, 97%, 98% or 99%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the molar ratio of the active oxide precursor in step (1) to the lithium salt in step (2) is 1:(0.95-1.10), for example, 1:0.95, 1:1 or 1:1.10, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the primary sintering temperature in step (2) is 700-850°C, for example, 700°C, 800°C or 850°C, and the sintering time is 9-15h, for example, 9h, 12h or 15h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the atmosphere of the primary sintering in step (2) comprises an oxygen-containing atmosphere, and the oxygen concentration of the oxygen-containing atmosphere is ≥ 95%, for example, it can be 95%, 96%, 97%, 98% or 99%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the lithium salt in step (2) includes any one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium oxalate or lithium acetate, or a combination of at least two thereof.
[0026] Preferably, the molar ratio of the semi-finished product in step (2) to the coating agent in step (3) is 1:(0.001-0.050), for example, it can be 1:0.001, 1:0.005, 1:0.01, 1:0.03 or 1:0.05, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the coating agent in step (3) comprises a second metal additive and / or a fast ion conductor, preferably a second metal additive and a fast ion conductor.
[0028] The present invention adopts a composite coating process of a second metal additive and a fast ion conductor lithium tungstate. The second metal additive coating can reduce the side reaction between the material and the electrolyte, and the fast ion conductor coating increases the Li + The conductivity of the material is improved, while the interface stability and cycle performance of the material are improved.
[0029] Preferably, the molar ratio of the second metal additive to the fast ion conductor is (1-5):(1-5), for example, 1:1, 1:3, 1:5, 3:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the fast ion conductor comprises lithium tungstate.
[0031] Preferably, the metal element in the second metal additive includes any one of Al, B, Ti, Ce, Co or Y, or a combination of at least two of them.
[0032] Preferably, the temperature of the secondary sintering in step (3) is 250-700°C, for example, 250°C, 300°C, 500°C or 700°C, and the time is 6-12h, for example, 6h, 8h, 10h or 12h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, the atmosphere for the secondary sintering in step (3) includes dry air or oxygen.
[0034] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0035] (1) mixing a high nickel hydroxide precursor and a first metal additive in a molar ratio of 1:(0.001-0.050), and then pre-calcining at a temperature of 450-600° C. for 4-8 hours in an oxygen atmosphere with an oxygen concentration of ≥95% to obtain an active oxide precursor;
[0036] The general formula of the high nickel hydroxide precursor is Ni x Co y Mn z (OH)2, wherein x+y+z=1, x>0.90, y<0.09, z<0.09; the median particle size of the high nickel hydroxide precursor is 2.5-5 μm, and the BET is 11-20 μm 2 / g, bulk density ≥1.1g / cm 3 ;
[0037] (2) mixing the lithium salt and the active oxide precursor of step (1) in a molar ratio of 1:(0.95-1.10), and then sintering at a temperature of 700-850° C. for 9-15 hours in an oxygen atmosphere with an oxygen concentration of ≥95% to obtain a semi-finished product;
[0038] (3) mixing the coating agent and the semi-finished product of step (2) at a molar ratio of 1:(0.001-0.050), and then secondary sintering at a temperature of 250-700° C. for 6-12 hours in dry air or oxygen to obtain the high-nickel single crystal positive electrode material;
[0039] The coating agent includes a second metal additive and a fast ion conductor.
[0040] In a second aspect, the present invention provides a high-nickel single crystal positive electrode material, wherein the high-nickel single crystal positive electrode material is prepared by the preparation method described in the first aspect.
[0041] Preferably, the high nickel single crystal positive electrode material is a core-shell structure, wherein the general formula of the core is Li b Ni x Co y Mn z M m O2, wherein 0.95<b<1.10, for example, it can be 0.96, 0.98, 1.0, 1.05 or 1.09, 0.90<x<1, for example, it can be 0.91, 0.9 or 0.99, y<0.09, for example, it can be 0.06, 0.07 or 0.08, z<0.09, for example, it can be 0.06, 0.07 or 0.089, 0.0005≤m≤0.005, for example, it can be 0.0005, 0.001, 0.003 or 0.005, M includes any one of Y, Sr, Zr, Ti, W, Al or Mg, or a combination of at least two of them, and the shell includes lithium tungstate and an oxide containing N, wherein N includes any one of Al, B, Ti, Ce, Co or Y, or a combination of at least two of them.
[0042] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the high-nickel single crystal positive electrode material as described in the second aspect.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention adopts a high-activity precursor pretreatment sintering process, firstly through the reaction of the precursor material and the first metal additive, to generate a highly active oxide precursor, which is beneficial to the sintering of the single crystal semi-finished product with the lithium salt. +Deintercalation reduces lithium-nickel mixing, inhibits phase change of crystal structure, reduces residual alkali, and performs two sintering and coating processes to reduce side reactions between materials and electrolytes, thereby increasing Li + The conductivity of the material is improved, while the interface stability of the material is improved, thereby enhancing the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a SEM image of the high-nickel single crystal positive electrode material described in Example 1 of the present invention;
[0046] Figure 2 This is a battery cycle performance diagram made of the high-nickel single crystal positive electrode material described in Example 1, Example 8, Example 9 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material, the preparation method comprising the following steps:
[0050] (1) mixing a high nickel hydroxide precursor and a first metal additive in a high speed mixer at a molar ratio of 1:0.005, placing the uniformly mixed materials into a sagger, and then pre-calcining them at a temperature of 500° C. for 5 h in an oxygen atmosphere with an oxygen concentration of 99% to obtain an active oxide precursor;
[0051] The general formula of the high nickel hydroxide precursor is Ni 0.93 Co 0.05 Mn 0.02 (OH)2; the median particle size of the high nickel hydroxide precursor is 3.5 μm, and the BET is 15m 2 / g, bulk density is 1.5g / cm 3 ; The first metal additive is zirconium oxide;
[0052] (2) mixing lithium hydroxide and the active oxide precursor of step (1) at a molar ratio of 1:1.03, placing the mixed material in a sagger, and then sintering once at a temperature of 800° C. for 14 hours in an oxygen atmosphere with an oxygen concentration of 98% to obtain a semi-finished product;
[0053] (3) The coating agent and the semi-finished product of step (2) are mixed at a molar ratio of 1:0.004, and after being mixed evenly, they are placed in a sagger, and then secondary sintered at a temperature of 650° C. for 8 h in dry air to obtain the high-nickel single crystal positive electrode material. The SEM image of the high-nickel single crystal positive electrode material is as shown in FIG. Figure 1 As shown;
[0054] The coating agent includes a second metal additive and lithium tungstate in a molar ratio of 3:1, and the second metal additive is cobalt oxide.
[0055] Example 2
[0056] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material, the preparation method comprising the following steps:
[0057] (1) mixing a high nickel hydroxide precursor and a first metal additive in a high speed mixer at a molar ratio of 1:0.001, placing the uniformly mixed materials into a sagger, and then pre-calcining them at a temperature of 600° C. for 4 hours in an oxygen atmosphere with an oxygen concentration of 95% to obtain an active oxide precursor; the first metal additive is yttrium oxide;
[0058] The general formula of the high nickel hydroxide precursor is Ni 0.94 Co 0.04 Mn 0.02 (OH)2; the median particle size of the high nickel hydroxide precursor is 2.5 μm, and the BET is 20m 2 / g, bulk density is 1.1g / cm 3 ;
[0059] (2) mixing lithium hydroxide and the active oxide precursor of step (1) at a molar ratio of 1:1.1, placing the mixed material in a sagger, and then sintering once at a temperature of 850° C. for 9 hours in an oxygen atmosphere with an oxygen concentration of 95% to obtain a semi-finished product;
[0060] (3) mixing the coating agent and the semi-finished product of step (2) at a molar ratio of 1:0.050, placing the mixture in a sagger after uniform mixing, and then sintering the mixture for a second time at 700° C. for 6 h in dry air to obtain the high-nickel single crystal positive electrode material;
[0061] The coating agent includes a second metal additive and lithium tungstate in a molar ratio of 1:1, and the second metal additive is cobalt oxide.
[0062] Example 3
[0063] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material, the preparation method comprising the following steps:
[0064] (1) mixing a high nickel hydroxide precursor and a first metal additive in a high speed mixer at a molar ratio of 1:0.050, placing the uniformly mixed materials into a sagger, and then pre-calcining them at a temperature of 450° C. for 8 hours in an oxygen atmosphere with an oxygen concentration of 95% to obtain an active oxide precursor; the first metal additive is zirconium oxide;
[0065] The general formula of the high nickel hydroxide precursor is Ni 0.94 Co 0.04 Mn 0.02 (OH)2; the median particle size of the high nickel hydroxide precursor is 2.5 μm, and the BET is 20m 2 / g, bulk density is 1.1g / cm 3 ;
[0066] (2) mixing lithium hydroxide and the active oxide precursor of step (1) in a molar ratio of 1:1, placing the mixed material in a sagger, and then sintering once at a temperature of 700° C. for 15 h in an oxygen atmosphere with an oxygen concentration of 98% to obtain a semi-finished product;
[0067] (3) mixing the coating agent and the semi-finished product of step (2) at a molar ratio of 1:0.001, placing the mixture in a sagger after mixing evenly, and then sintering the mixture for a second time at 250° C. for 12 h in dry air to obtain the high-nickel single crystal positive electrode material;
[0068] The coating agent includes a second metal additive and lithium tungstate in a molar ratio of 1:3, and the second metal additive is cobalt oxide.
[0069] Example 4
[0070] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the molar ratio of the high-nickel hydroxide precursor to the first metal additive in step (1) is 1:0.0005.
[0071] Example 5
[0072] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the molar ratio of the high-nickel hydroxide precursor to the first metal additive in step (1) is 1:0.1.
[0073] Example 6
[0074] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the pre-firing temperature in step (1) is 400°C.
[0075] Example 7
[0076] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the pre-firing temperature in step (1) is 700°C.
[0077] Example 8
[0078] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the coating agent in step (3) only includes the second metal additive.
[0079] Example 9
[0080] This embodiment provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as that of Embodiment 1 except that the coating agent in step (3) only includes lithium tungstate.
[0081] Comparative Example 1
[0082] This comparative example provides a method for preparing a high-nickel single crystal positive electrode material, which is the same as Example 1 except that in step (1), the high-nickel hydroxide precursor and the first metal additive are not pre-fired but are directly mixed with a lithium salt for a single sintering in step (2).
[0083] Comparative Example 2
[0084] This comparative example provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as Example 1 except that the first metal additive is not added in step (1).
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a high-nickel single crystal positive electrode material. The preparation method is the same as Example 1 except that in step (3), the second metal additive is added during the first sintering of step (2) and is not coated together with lithium tungstate in step (3).
[0087] The high-nickel single crystal positive electrode materials obtained in the above embodiments and comparative examples were tested for residual alkali content according to the following residual alkali test method. The specific test steps are as follows: use an automatic potentiometric titrator 905titrandor for testing, weigh 30g of sample, add 100mL of ultrapure water, stir for 30min, let stand until the solution is stratified, filter, take 100mL of filtrate and use a potentiometric titrator to titrate with 0.04mol / L hydrochloric acid, record the volumes of the two equivalence points, and calculate the Li2CO3 and LiOH contents by the instrument.
[0088] The high nickel single crystal positive electrode materials prepared in the above examples and comparative examples were respectively assembled into CR2032 type button batteries, and then the 50-week capacity retention rate was tested at 45°C, 3.0-4.3V, 1.0C charging, and 1.0C discharge rate. The battery cycle performance diagrams made of the high nickel single crystal positive electrode materials described in Example 1, Example 8, Example 9 and Comparative Example 1 are as shown in FIG. Figure 2 shown.
[0089] The test results are shown in Table 1:
[0090] Table 1
[0091]
[0092]
[0093] From Table 1 we can see that:
[0094] (1) The high-nickel single crystal positive electrode material obtained by the present invention has a low residual alkali content on the surface, wherein the content of Li2CO3 can be as low as 2405ppm, the content of LiOH can be as low as 3128ppm, and the capacity retention rate after 50 cycles at 45°C is as high as 95.9%; It can be seen from Example 1 and Comparative Example 1 that if Comparative Example 1 is not pre-burned, the precursor is a hydroxide of nickel, cobalt and manganese, and -OH easily reacts with CO2 and moisture in the air to be converted into Li2CO3 and LiOH, resulting in an increase in the residual alkali level. The residual alkali level is high in the early stage and increases synchronously in the later stage, resulting in poor cycle performance of the finished product; It can be seen from Example 1 and Comparative Example 2 that when no additive is added during the pre-burning process, the activity of the precursor cannot be improved, and the performance of the obtained material is reduced.
[0095] (2) It can be seen from Example 1 and Comparative Example 3 that the present invention preferably uses two coating agents for coating together, because the metal oxide coating acts as a physical barrier, which can inhibit side reactions, prevent chemical corrosion of the electrolyte, and reduce the dissolution of transition metals. However, the lithium ion conductivity is poor. Lithium tungstate, as a solid electrolyte, does not have electrochemical activity. After composite coating with metal oxides, the ionic conductivity of the material can be improved, the surface chemical modification can be carried out, the charge transfer at the interface of the positive electrode material can be promoted, and the polarization of the material during charging and discharging can be reduced. It can be seen from Example 1 and Examples 4-7 that the amount of additives added during pre-firing and the pre-firing temperature will affect the material properties. It can be seen from Examples 1 and Examples 8-9 that the present invention preferably uses a composite coating agent for coating.
[0096] In summary, the present invention provides a high-nickel single crystal positive electrode material and a preparation method and application thereof. The preparation method first prepares a high-activity precursor, which is beneficial to the sintering of the single crystal semi-finished product with the lithium salt. +Deintercalation and subsequent coating can reduce side reactions between the material and the electrolyte, while improving the interface stability of the material, thereby enhancing the cycle performance of the battery.
[0097] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a high-nickel single crystal positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing and pre-calcining a precursor material and a first metal additive to obtain an active oxide precursor; (2) mixing the lithium salt and the active oxide precursor of step (1) and sintering once to obtain a semi-finished product; (3) The coating agent and the semi-finished product of step (2) are mixed and subjected to secondary sintering to obtain the high-nickel single crystal positive electrode material.
2. The preparation method according to claim 1, characterized in that: The precursor material in step (1) includes a high nickel hydroxide precursor; Preferably, the general formula of the high nickel hydroxide precursor is Ni x Co y Mn z (OH)2, where, x+y+z=1, x>0.90, y<0.09, z<0.09; Preferably, the median particle size of the precursor material in step (1) is 2.5-5 μm, and the BET is 11-20 μm. 2 / g, bulk density ≥1.1g / cm 3 .
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the precursor material to the first metal additive in step (1) is 1:(0.001-0.050); Preferably, the metal element in the first metal additive in step (1) includes any one or a combination of at least two of Y, Sr, Zr, Ti, W, Al or Mg; Preferably, the pre-burning temperature in step (1) is 450-600° C. and the time is 4-8 hours; Preferably, the pre-firing atmosphere in step (1) comprises an oxygen-containing atmosphere, and the oxygen concentration of the oxygen-containing atmosphere is ≥ 95%.
4. The preparation method according to any one of claims 1 to 3, characterized in that The molar ratio of the active oxide precursor in step (1) to the lithium salt in step (2) is 1:(0.95-1.10); Preferably, the primary sintering temperature in step (2) is 700-850° C. and the sintering time is 9-15 h; Preferably, the atmosphere of the primary sintering in step (2) comprises an oxygen-containing atmosphere, and the oxygen concentration of the oxygen-containing atmosphere is ≥ 95%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the semi-finished product in step (2) to the coating agent in step (3) is 1:(0.001-0.050); Preferably, the coating agent in step (3) comprises a second metal additive and / or a fast ion conductor, preferably a second metal additive and a fast ion conductor; Preferably, the fast ion conductor comprises lithium tungstate; Preferably, the metal element in the second metal additive includes any one of Al, B, Ti, Ce, Co or Y, or a combination of at least two of them.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The secondary sintering temperature in step (3) is 250-700° C. and the time is 6-12 hours; Preferably, the atmosphere for the secondary sintering in step (3) includes dry air or oxygen.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) mixing a high nickel hydroxide precursor and a first metal additive in a molar ratio of 1:(0.001-0.050), and then pre-calcining at a temperature of 450-600° C. for 4-8 hours in an oxygen atmosphere with an oxygen concentration of ≥95% to obtain an active oxide precursor; The general formula of the high nickel hydroxide precursor is Ni x Co y Mn z (OH)2, wherein x+y+z=1, x>0.90, y<0.09, z<0.09; the median particle size of the high nickel hydroxide precursor is 2.5-5 μm, and the BET is 11-20 μm 2 / g, bulk density ≥1.1g / cm 3 ; (2) mixing the lithium salt and the active oxide precursor of step (1) in a molar ratio of 1:(0.95-1.10), and then sintering at a temperature of 700-850° C. for 9-15 hours in an oxygen atmosphere with an oxygen concentration of ≥95% to obtain a semi-finished product; (3) mixing the coating agent and the semi-finished product of step (2) at a molar ratio of 1:(0.001-0.050), and then secondary sintering at a temperature of 250-700° C. for 6-12 hours in dry air or oxygen to obtain the high-nickel single crystal positive electrode material; The coating agent includes a second metal additive and a fast ion conductor.
8. A high nickel single crystal positive electrode material, characterized in that: The high-nickel single crystal positive electrode material is prepared by the preparation method according to any one of claims 1 to 7.
9. The high nickel single crystal positive electrode material according to claim 8, characterized in that: The high nickel single crystal positive electrode material is a core-shell structure, wherein the general formula of the core is Li b Ni x Co y Mn z M m O2, wherein 0.95<b<1.10, 0.90<x<1, y<0.09, z<0.09, 0.0005≤m≤0.005, M includes any one of Y, Sr, Zr, Ti, W, Al or Mg or a combination of at least two thereof, and the shell includes lithium tungstate and an oxide containing N, wherein N includes any one of Al, B, Ti, Ce, Co or Y or a combination of at least two thereof.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the high-nickel single crystal positive electrode material as claimed in claim 8 or 9.
Citation Information
Cited By
Single-crystal positive electrode material as well as preparation method and application thereof
CN120767306A